ความเป็นเมืองจากการประเมินคุณค่าและมูลค่าที่ดินในพื้นที่อำเภอเมืองสุพรรณบุรีด้วยเทคโนโลยีภูมิสารสนเทศ - ไชยคราม, ธัญญรัตน์ (Thai Journal of Science and Technology, 2021)
This study aims to (1) classify urban areas from satellite images from Landsat-7 ETM, Landsa-8 OLI, and Sentinel 2 during 2012, 2016, and 2019, divided into two types of land use which are urban land use and non-urban land use. Utilizing supervised classification technique, urban land use was found 88.07 m2 in Muang Suphanburi district, which was the largest urban land use as 9.74 % of the whole area of Suphanburi province; (2) to analyze urban land using measurement of HBU (highest and best use) combined with multiple-criteria decision making by applying SAW (simple additive weighting). According to land appraisal factors, the most area in Muang Suphanburi district was the highest and the best in land use, as 263.810 m2 or 48.77 % of the whole province was in medium utilization level, 191.256 m2 or 35.36 % was in low utilization level. There was 85.768 m2 or 15.87 % in the best and highest level mostly located in Tha Phi Liang subdistrict, Sanamchai subdistrict, Tha Rahat subdistrict, Rua Yai subdistrict, and Pho Phraya subdistrict; (3) to analyze the factors which influence land pricing by using multiple regression analysis at statistical significance 0.05. The most influential factors of land pricing were the land with the connecting exit to the main road or the exit near all types of transportation or minor road. Secondly, the land had to be in a service area of public utility and public assistance such as distance from public transportation, government facility, business area, and public park area and distance from service sectors or religious places orderly. These factors were aligned with land appraisal measurement from the Property Valuation Division of the Treasury Department, Ministry of Finance in 2016-2019, and it is found out that the plot of land which located in the area of highest utility level or highest land price, was assessed as high as 1,050-30,000 Baht per square two-meters. Also, the land linked to the minor road, especially land plots connected to Phra Phan Wasa road, Malaiman road, Muenhan road, and land plots located in the lowest utility level or low-value lands, were appraised at 150-500 Baht per square two-meters.